Price formation in auction theory : a review of theoretical findings and a model for future research - Xin, Yu (2012)
This paper studies the price formation in both perfect and imperfect competitive market. Some interesting ideas, which were raised in previous journals, are revisited. The relationship between the traditional economic theories and auctions is fully covered as well. In this area of study, the third-degree price discrimination theory was shown equivalent to the one of optimal auction in Bulow & Roberts (1989). Based on some significant findings in that research, we extend the model of Cournot competition under auction theory, and compare and contrast this new model with the one under microeconomic theory.